The economics of intellectual property rights under imperfect enforcement: developing countries, biotechnology, and the TRIPs agreement - Giannakas, Konstantinos (International Food Policy Research Institute, 2001)
This paper develops a model of heterogeneous producers to examine the economic causes of IPR infringement and its consequences for the welfare of the interest groups and the pricing and adoption of a new technology (i.e., a genetically modified seed) in the context of a small open developing economy. Enforcement of IPRs, and pricing and adoption of the new technology are modeled as a sequential game between the government that enforces the IPRs, a foreign innovating firm that prices the new technology, and the developing country’s producers who make the production and cheating decisions. Analytical results show that complete deterrence of IPR infringement is not always economically optimal. IPR infringement affects the welfare of the interest groups and has important ramifications for the pricing and adoption of the new technology. The quantitative nature of the results depends critically on the existing labeling regime. The analysis also shows that differences in the level of IPR enforcement provide an alternative justification for (and explanation of) differences in the pricing of the new technology in different countries around the world - a strategy adopted by leading innovators in the sector. Finally, the results suggest that if the penalties for IPR infringement under the TRIPs agreement follow the custom of retaliatory sanctions under the GATT, enforcement of IPRs will remain imperfect and the innovators’ ability to obtain value for their biotech traits will still be limited.